Experiences, attitudes, and perceptions of caregivers of individuals with treatment-resistant schizophrenia: a qualitative study - Cecilia Brain; Steven Kymes; Dana B. DiBenedetti; Thomas Brevig; Dawn I. Velligan (BMC Psychiatry, 2018)
Abstract Background Treatment-resistant schizophrenia (TRS) affects about one-third of individuals with schizophrenia. People with TRS do not experience sustained symptom relief and at the same time have the most severe disease-related disability and associated costs among individuals with severe mental disorders. Like caregivers of people with treatment-responsive schizophrenia, caregivers of individuals with TRS experience the disease burden along with their care recipients; however, for those providing care for individuals with TRS, the stress of the burden is unrelenting due to uncontrolled symptoms and a lack of effective treatment options. The objective of this study is to better understand the burden of TRS from the caregiver perspective and to explore their perception of available treatments. Methods Eight focus groups with non-professional, informal caregivers of individuals with TRS were conducted in 5 US locations. TRS was defined as failure of ≥2 antipsychotics and persistent moderate-to-severe positive symptoms of schizophrenia, per caregiver report. Results The 27 caregivers reported an average of 37 h/week providing direct care, and 21 reported being on call “24/7.” Caregivers commonly reported that their care recipients exhibited symptoms of auditory hallucinations (89%), agitation/irritability/hostility (81%), suspiciousness (78%), tangentiality (74%), and cognitive impairment (74%); 70% of caregivers ranked suspiciousness/persecution as the most challenging symptom category. Caring for an individual with TRS impacted many caregivers’ finances, career prospects, social relationships, and sense of freedom. Additionally, multiple medication failures led to a sense of hopelessness for many caregivers. Conclusions Persistent positive symptoms caused significant perceived burden, feelings of being overwhelmed and having no relief, and substantial negative impacts on caregivers’ emotional and physical health. To address these substantial unmet needs, policy makers should be aware of the need for practical, social, and emotional support for these caregivers and their families. Additionally, new treatment options for TRS should be developed.